Protein Kinase Cδ Deficiency Causes Mendelian Systemic Lupus Erythematosus With B Cell‐Defective Apoptosis and Hyperproliferation. Issue 8 (26th July 2013) - Belot, Alexandre; Kasher, Paul R.; Trotter, Eleanor W.; Foray, Anne‐Perrine; Debaud, Anne‐Laure; Rice, Gillian I.; Szynkiewicz, Marcin; Zabot, Marie‐Therese; Rouvet, Isabelle; Bhaskar, Sanjeev S.; Daly, Sarah B.; Dickerson, Jonathan E.; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a prototype autoimmune disease that is assumed to occur via a complex interplay of environmental and genetic factors. Rare causes of monogenic SLE have been described, providing unique insights into fundamental mechanisms of immune tolerance. The aim of this study was to identify the cause of an autosomal‐recessive form of SLE. Methods: We studied 3 siblings with juvenile‐onset SLE from 1 consanguineous kindred and used next‐generation sequencing to identify mutations in the disease‐associated gene. We performed extensive biochemical, immunologic, and functional assays to assess the impact of the identified mutations on B cell biology. Results: We identified a homozygous missense mutation in PRKCD, encoding protein kinase δ (PKCδ), in all 3 affected siblings. Mutation of PRKCD resulted in reduced expression and activity of the encoded protein PKCδ (involved in the deletion of autoreactive B cells), leading to resistance to B cell receptor– and calcium‐dependent apoptosis and increased B cell proliferation. Thus, as for mice deficient in PKCδ, which exhibit an SLE phenotype and B cell expansion, we observed an increased number of immature B cells in the affected family members and a developmental shift toward naive B cells with an immature phenotype. Conclusion: Our findings indicate that PKCδ is crucial in regulating B cell tolerance and preventing self‐reactivity in humans, and that PKCδ deficiency represents a novel genetic defect of apoptosis leading to SLE.